Scaffolding in the development of learning and innovative skills (4Cs): An action research study in a Chilean teacher education program - Jessica Vega-Abarzúa; Camilo Jarpa Gutiérrez; Valentina Palma Pulgar; Vasco Salazar Marabolí (Universitas Ahmad Dahlan, 2023)
Situated in an action research study, this investigation describes the impact of scaffolding on the perceptions of preservice teachers of English. An action plan was developed for this group of preservice teachers as they showed concern for some of their communication, critical thinking, creativity and collaboration skills known as learning and innovative skills or 4Cs. The action plan comprised the use of scaffolding as the main means of instruction, which was executed by the design of various evidenced-based scaffolds including group discussions, note-taking, summarizing, comparing, hypothesizing and problem-solving. The group of preservice teachers included 11 students, 4 male and 7 female, aged 20 and 38 of an English education program in a private university in Ñuble, Chile. Data was collected in three main stages using an open-ended questionnaire before, during and after the implementation of the action plan. Findings showed that the use of scaffolding increased participants’ perceptions of their overall 4Cs skills, being critical thinking the most salient area of change. It is hoped that English teacher education programs can incorporate scaffolding as a potential instructional method in the development of academic and crucial skills for future teacher generations.